2022
DOI: 10.1007/s40333-022-0006-z
|View full text |Cite|
|
Sign up to set email alerts
|

Dieback intensity but not functional and taxonomic diversity indices predict forest productivity in different management conditions: Evidence from a semi-arid oak forest ecosystem

Abstract: The relationships between different aspects of diversity (taxonomic, structural and functional) and the aboveground biomass (AGB) as a major component of global carbon balance have been studied extensively but rarely under the simultaneous influence of forest dieback and management. In this study, we investigate the relationships between taxonomic, functional and structural diversity of woody species (trees and shrubs) and AGB along a gradient of dieback intensity (low, moderate, high and no dieback as control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 97 publications
1
3
0
Order By: Relevance
“…Our observations are in line with Karami et al (2022) who reported the highest rate of oak tree dieback in forest stands with a higher admixture index, as spatial diversity or dissimilarity of tree species in semi-arid areas. Moreover, crown size (Fan et al, 2008), forest structure, and ecological conditions such as soil properties (Turner and Lambert, 2005;Kabrick et al 2008;Gazol et al, 2018;Cunningham et al, 2010) have also proven to be effective in the occurrence of tree dieback.…”
Section: Dieback Severity In Relation To Catena Shape and Positionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our observations are in line with Karami et al (2022) who reported the highest rate of oak tree dieback in forest stands with a higher admixture index, as spatial diversity or dissimilarity of tree species in semi-arid areas. Moreover, crown size (Fan et al, 2008), forest structure, and ecological conditions such as soil properties (Turner and Lambert, 2005;Kabrick et al 2008;Gazol et al, 2018;Cunningham et al, 2010) have also proven to be effective in the occurrence of tree dieback.…”
Section: Dieback Severity In Relation To Catena Shape and Positionsupporting
confidence: 93%
“…The dieback severity was estimated based on visual criteria of dieback in each plot according to the field method developed by Karami et al (2022), such as, were recorded the important signs of decline, including the separation of the trunk bark and the sap outflow, the color change of leaves, and the partial or complete drying of the crown.…”
Section: Dieback Severitymentioning
confidence: 99%
See 1 more Smart Citation
“…Climate change has negatively affected these forests by increasing temperature and decreasing rainfall [35]. The occurrence of oak decline and secondary pests and diseases in this region in recent decades, according to many researchers, has been associated with the phenomenon of climate change [36][37][38]. In addition, human activities such as land use change, wood harvesting and livestock grazing have destroyed large parts of these forest ecosystems [34,39,40].…”
Section: Introductionmentioning
confidence: 99%